Expand menu menu_open Minimize Start chapters Home History history History expand_more
{{ item.displayTitle }}
navigate_next
No history yet!
Progress & Statistics equalizer Progress expand_more
Student
navigate_next
Teacher
navigate_next
{{ filterOption.label }}
{{ item.displayTitle }}
{{ item.subject.displayTitle }}
arrow_forward
No results
{{ searchError }}
search
menu_open
{{ courseTrack.displayTitle }}
{{ statistics.percent }}% Sign in to view progress
{{ printedBook.courseTrack.name }} {{ printedBook.name }}
search Use offline Tools apps
Login account_circle menu_open

Describing Graphs of Polynomial Functions

Describing Graphs of Polynomial Functions 1.11 - Solution

arrow_back Return to Describing Graphs of Polynomial Functions

Before we begin, let's recall two important definitions.

  • A function ff has even symmetry when f(-x)=f(x)f(\text{-} x)=f(x) for all xx in its domain.
  • A function ff has odd symmetry when f(-x)=-f(x)f(\text{-} x)=\text{-} f(x) for all xx in its domain.
Let's see how the graphs of these types of functions look.
Even functions

Odd functions

Reset

Consider the graphs above. We can see that for even symmetry, if (x,y)(x,y) is on the graph, then (-x,y)(\text{-} x,y) is also on the graph. Meanwhile, for an odd symmetry, if (x,y)(x,y) is on the graph, then (-x,-y)(\text{-} x, \text{-} y) is also on the graph. Now, consider the given function. s(x)=-x3+2x9\begin{gathered} s(x)=\text{-} x^3+2x-9 \end{gathered} Let's calculate s(-x).s({\color{#0000FF}{\text{-} x}}).
s(-x)=-(-x)3+2(-x)9s({\color{#0000FF}{\text{-} x}})=\text{-} ({\color{#0000FF}{\text{-} x}})^3+2({\color{#0000FF}{\text{-} x}})-9
Simplify right-hand side
s(-x)=-(-x3)+2(-x)9s(\text{-} x)=\text{-} \left (\text{-} x^3\right)+2(\text{-} x)-9
s(-x)=x3+2(-x)9s(\text{-} x)=x^3+2(\text{-} x)-9
s(-x)=x32x9s(\text{-} x)=x^3-2x-9
Next, let's calculate -s(x).{\color{#FF0000}{\text{-}}} s(x).
-s(x)=-(-x3+2x9){\color{#FF0000}{\text{-}}} s(x)={\color{#FF0000}{\text{-}}} \left( \text{-} x^3+2x-9\right)
-s(x)=x32x+9\text{-} s(x)=x^3-2x+9
Finally, let's think about what these results tell us.
s(x)s(x) s(-x)s(\text{-} x) -s(x)\text{-} s(x)
-x3+2x9\text{-} x^3+2x-9 x32x9x^3-2x-9 x32x+9x^3-2x+9

Since s(x)s(-x)s(x)\neq s(\text{-} x) and s(-x)-s(x),s(\text{-} x)\neq \text{-} s(x), the function ss has neither an even nor an odd symmetry.